Developing Second Language Proficiency in the Context of Plurilingual Education: An Action Research Study in a Model Primary School in Rwanda - Mutseekwa, Christopher (The Canadian Journal of Action Research, 2026)
This article recounts the researcher's experiences with two specialist English teachers at a model school in Rwanda, navigating how English as a Second Language can be taught using a variety of pedagogical strategies. Following Participatory Action Research (PAR), the study documents how Primary 4 (P4) and Primary 6 (P6) learners and their teachers actively construct the discourse for L2 learning. The engagements between the researcher and participating teachers are interpreted through the lens of the socio-cognitive theory for second language learning and plurilingual education. Multi-layered levels of data analysis occur simultaneously with data collection throughout the stages of the PAR. Findings reveal challenges that impede L2 development, including limited vocabulary, inadequate time for practicing the target language, and difficulties constructing extended responses. Findings also reveal useful approaches for developing L2 proficiency, including teaching receptive and productive skills sequentially, modelling and demonstrating the target language, and engaging in translanguaging. We conclude that in contexts similar to this study where learners are struggling with L2, mother tongue can be used as an additional language resource through plurilingual pedagogies.